POLA INTERAKSI GURU DAN SISWA TUNANETRA DALAM PEMBELAJARAN MATEMATIKA DI SMPLB A YKAB SURAKARTA (Studi Kasus Pada Siswa Kelas IX SMPLB A YKAB Surakarta Semester Ganjil Tahun Pelajaran 2012/2013) - Khoiriyah, Siti; Sujadi, Imam; Pangadi, Pangadi (Jurnal Pembelajaran Matematika, 2013)
with visual impairment in mathematics teaching learning on a conceptual and procedural knowledge in class IX SMPLB A YKAB Surakarta. This research was a qualitative case study, investigating deeply about the interaction of the teacher and the students in order that the interaction pattern can be described in the mathematics teaching learning. The subjects of this research were a mathematics teacher and all students of class IX SMPLB A YKAB Surakarta. The data in this study were in the form of teacher and students interactions obtained from transcriptions of the teaching learning recordings during twice observations. The transcription results were the teacher and the studentsâ conversations that are further reduced in order to obtain certain conversation related to the teaching learning of conceptual and procedural knowledge. Furthermore, labeling speech act and speech interaction was conducted in the conversation of conceptual and procedural teaching learning. Based on the labeling, speech interaction were categorized into three, namely: 1) speech interaction that was begun with speech act of giving information (BIn), 2) speech interaction that was begun with speech act of performing information (UIn), and 3) speech interaction that was begun with speech act of stimulating information (TIn). Each of the categories was analyzed so that the subjects that are interacting can be examined. The result of the analysis became the data of teacher and students interaction. The technique used to validate the data was time triangulation done by matching the data of the teacher and the studentsâ interaction taken from the first observation and the data of the teacher and the studentsâ interaction taken from the second observation.The results of the matching process were used to describe the interaction pattern. The findings of this research were: 1) the interaction pattern of the teacher and the students with visual impairment in mathematics teaching learning on a conceptual knowledge in class IX SMPLB A YKAB Surakarta was a two-way interaction pattern with inter-students interactions.Two-way interactionwith studentteachersis dominatedby theactivities ofthe teacherto giving information (BIN) and the performing information (TIN) to the students. While theinteractionbetween studentsis dominatedbythe activities ofthe studentsto performanceinformation(UIN). 2) the interaction pattern of the teacher and the students with visual impairment in mathematics teaching learning on a procedural knowledge in class IX SMPLB A YKAB Surakarta was a multiple-way interaction pattern (optimal result). Teacherinteractionwith studentsis dominatedby theactivities ofthe teacherto giving information(BIN), andstimulating information(TIN) to the students. Whilestudent interactionwith studentsspreadis dominated bythe performanceof information(UIN).Keywords:interactionpattern, conceptual knowledge, procedural knowledge, mathematics teachinglearning, students with visual impairment